Description of the diploid chromosome set of Triatoma pintodiasi (Hemiptera, Triatominae) - Alevi, K. C. C. [UNESP]; Moreira, F. F. F.; Jurberg, J.; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2016)
Triatoma pintodiasi has been described and recently grouped in the Rubrovaria subcomplex. T. pintodiasi was initially compared to T. carcavalloi by staining and subsequently identified as T. circummaculata. However, after thorough examination, it was observed to be a cryptic species of T. circummaculata, and was described based on morphological features, morphometric data, and biochemical patterns of hemolymph. Thus, this paper aims to describe the karyotype of, and spermatogenesis in, T. pintodiasi, in order to elucidate the reproductive biology and taxonomy of the species. Sex chromosomes of T. pintodiasi formed a heteropyknotic chromocenter, and compaction of chromatin was observed during prophase. However, in contrast to observations in T. carcavalloi and T. circummaculata, in T. pintodiasi it was observed individualization of the sex chromosomes. The diploid chromosome set of the species 2n = 22 (20A + XY) is described through analysis of metaphases I and II. Initial cytogenetic characteristics of T. pintodiasi are described and the observed differences in the chromocenter are suggested as a possible cytotaxonomic tool. To gain a better understanding of the specific status of this cryptic species, however, we emphasize the need for further cytogenetic, molecular, biological, and biogeographical analysis, in addition to experimental hybrid crosses with other species of the Rubrovaria subcomplex.
Keywords: Karyotype; Spermatogenesis; Rubrovaria subcomplex; Triatoma pintodiasi